Causality of unsaturated fatty acids and psoriasis a Mendelian randomization study - Li, Junchen; Shen, Qian; Guo, Chenqi; Wang, Yingdong; Ma, Yuxiao; Zhang, Yu (Frontiers in Nutrition, 2024)
Background Many observational studies have identified a link between unsaturated fatty acids and psoriasis. However, they contain reverse causality and confounding factors, and there is no definite causal study between unsaturated fatty acids and psoriasis. Objectives Analysis of causality between unsaturated fatty acids and psoriasis by Mendelian randomization. Methods We used IEU Open GWAS Project, omega-3 PUFA and omega-6 PUFA data from 114,999 subjects, MUFA data from 13,535 subjects, and psoriasis data from 4,510 cases and 212,242 controls were included. We employed the inverse-variance weighted (IVW) method as the primary analytical approach and four additional MR methods. Moreover, we performed heterogeneity and horizontal pleiotropy assessments using Cochrane’s Q and MR-Egger intercept tests, respectively. Finally, we performed sensitivity analyses to enhance our findings’ precision and veracity. Results IVW results showed no causal effect of omega-3 PUFA on psoriasis (p = 0.334; OR, 0.909; 95% CI, 0.748–1.104), omega-6 PUFA cause psoriasis (p = 0.046; OR, 1.174; 95% CI, 1.003–1.374), MUFA cause psoriasis (p = 0.032; OR, 1.218; 95% CI, 1.018–1.457), no causal effect of omega-3 PUFA in psoriasis (p = 0.695; OR, 0.989; 95% CI, 0.937–1.044), no causal effect of omega-6 PUFA in psoriasis (p = 0.643; OR, 1.013; 95% CI, 0.960–1.068), psoriasis is not causal to MUFA (p = 0.986; OR, 1.000; 95% CI, 0.949–1.055). Heterogeneity, horizontal pleiotropy, and sensitivity analyses showed reliable results. Conclusion We found that circulating omega-6 PUFA and MUFA cause psoriasis, while omega-3 PUFA do not. Treatments that lower circulating omega-6 PUFA and MUFA are effective in psoriasis. After a better understanding of fatty acid intake and circulation, the population can be advised to regulate their diet.